Development of MOOC Content in Case-Method-Based Psychodynamic Counseling Courses as Online Learning Media - Apriani, Rizka; Probowati, Devy; Rahman, Diniy Hidayatur; Az-Zahra, Faza Kasyiva; Qonita, Fauziah Ilmi; Daud, Nurul Ain Mohd (Buletin Konseling Inovatif, 2025)
The psychodynamic counseling course is one of the compulsory courses to provide students with an understanding of theories, concepts, and techniques based on psychodynamic views. With various existing goals, it shows that implementing this course requires technology-based media to support the optimal running of lectures. The MOOC (Massive Open Online Course) platform is an answer to implementing psychodynamic counseling courses with existing flexibility and accessibility. The purpose of this research is to develop content on the MOOC platform to improve the quality of learning by utilizing interactive technology and learning content can be presented dynamically using various media such as video, audio, and simulation. The development of MOOC content goes through a series of stages of research and development. The development design used is the ADDIE development model to produce a specific product and test the effectiveness of the product. The stages of this research are analysis, design, development, implementation, and evaluation. The results of the study show that the development of case-method-based MOOC content in the Psychodynamic Counseling course has succeeded in increasing the effectiveness of online learning for materials that require in-depth understanding and analytical skills. Despite the challenges in moderating discussions and the need for additional guidance for more abstract concepts, MOOCs have proven their potential as an effective and flexible online learning medium. As for the suggestions in this study, it is hoped that the development of MOOC content can be more extensive in other courses. In addition, MOOC platforms can be used more widely in optimizing learning.